The recent attempt at a reform of the Buddhist Sangha in Burma and its implications - Bechert, Heinz (Internationales Asien-Forum, 1989)
The Sangha reform of 1980 as such was, in principle, nothing new, but a revival of old traditions in a superficially modernized form. At the same time, it was designed for political ends in the context of the Burmese situation during the Ne Win era. It may be still too early for an adequate assessment of its various long-term consequences, but it is evident that it has failed to achieve its political objectives. While in Thailand it is the government which controls the monkhood, the Sangha of Burma has remained a strong potential force in politics, and it is obviously capable of being activated in times of crisis. It will be one of the crucial tests for any future Burmese government if and how it is able to handle the political influence of the Sangha.